Quality of aerobic training description and its relation to intervention efficacy in chronic obstructive pulmonary disease trials: study protocol for a systematic review, meta-analysis and meta-regression - André Nyberg; Peter Klijn; Anouk A F Stoffels; Jana de Brandt; Hieronymus W H van Hees; Johan Jakobsson (BMJ Open)
Introduction Chronic obstructive pulmonary disease (COPD) is a major global health concern, characterised by ventilatory constraints, decreased cardiovascular fitness and reduced limb muscle function, profoundly affecting patients’ quality of life. Aerobic training plays a crucial role in the treatment of COPD, but the variability in methodologies and incomplete reporting of key components in aerobic training trials limits the assessment of their effectiveness. This systematic review aims to critically evaluate the application of training principles and reporting of key components in aerobic training trials in randomised controlled trials (RCTs) in the COPD literature.Methods and analysis The protocol adheres to the Preferred Reporting Items for Systematic reviews and Meta-Analyses Protocol guidelines. The review will include RCTs utilising aerobic training in individuals with COPD. A comprehensive search, following a predefined search strategy will identify studies published from 2007 to 2024 in English from MEDLINE, Embase, CINAHL, CENTRAL and PEDro. Studies including people with COPD and any aerobic training intervention will be included. Two reviewers will independently screen abstracts and titles for inclusion. Two reviewers will independently conduct the screening of full-text documents and data extraction. Study quality will be assessed using the Tool for the assESsment of sTudy quality and bias in Exercise, specifically developed for exercise training studies. The certainty of the evidence will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation approach. A systematic synthesis will be provided, with meta-analyses and meta-regression when appropriate.Ethics and dissemination As this review will involve the analysis of published data, ethical approval is not required. The findings of this review will be disseminated through peer-reviewed publications and conference presentations.PROSPERO registration number CRD42021247343.